Pengaruh Persepsi Manfaat Dan Persepsi Kemudahan Terhadap Niat Beli Menggunakan Fitur Link Sticker Di Instagram Stories - Lucky Alfando; Suramaya Suci Kewal; Johan Gunady Ony (LPPM Universitas Multi Data Palembang, 2023)
This study aims to analyze the effect of perceived benefits and perceived convenience on purchase intentionsusing the link sticker feature in Instagram stories. This research is a type of empirical research. Data collectiontechniques using the survey method, by distributing questionnaires to respondents who are considered representative.The sampling technique uses convenience sampling. The results showed that perceived benefits did not have apositive effect on purchase intentions through the link sticker feature and perceived convenience had a positiveeffect on purchase intentions through the link sticker feature on Instagram stories.